Innovative Solutions for Companies to Reduce Gender Gaps (UK Study Case) - ANGHELUTA, Andrei; MIHOREANU, Larisa; COSTEA, Carmen (Journal of Economic Development, Environment and People, 2016)
For many years the gender gap has been a complex reality having economic implications and social decisiveness. No matter the percentage recently decreased, we still confront with social discriminations. In this paper we focused on the UK labour market so we developed a case study for a logistics company, using classification of the employees in different pay bands. Based on this study we created a state of the art human resource tool that can be applied worldwide and that help firms to analyse the root causes and to reduce the gender gap.